Pengaruh Profitabilitas, Kebiijakan Hutang, Kepemilikan Manajerial dan Ukuran Perusahaan Terhadap Nilai Perusahaan(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014) - Setyoko, Budi, Drs. Eko Sugiyanto, M.Si (2017)
The purpose of this study was to examine and analyze the influence of profitability, debt policy, managerial ownership, and the size of the company on firm value. The company's value in this study is proxied by Price Book Value (PBV). Population of this research are manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. Samples were taken by using purposive sampling technique and the total sample of 46 companies for three years in accordance with the criteria. Analysis techniques using classic assumption test and multiple regression analysis Based on the research results in the regression model in mind a few things, as follows: (1) variable profitability significantly influence the value of the company, (2) variable debt policy significantly influence the value of the company, (3) variable managerial ownership no significant effect on firm value of the company, (4) variable size companies significant effect on the value of the company